Antioxidant Potential of Glutathione and Crosstalk with Phytohormones in Enhancing Abiotic Stress Tolerance in Crop Plants - Gyanendra Kumar Rai; Pradeep Kumar; Sadiya M. Choudhary; Hira Singh; Komal Adab; Rafia Kosser; Isha Magotra; Ranjeet Ranjan Kumar; Monika Singh; Rajni Sharma; Giandomenico Corrado; Youssef Rouphael (Plants, 2023)
Glutathione (GSH) is an abundant tripeptide that can enhance plant tolerance to biotic and abiotic stress. Its main role is to counter free radicals and detoxify reactive oxygen species (ROS) generated in cells under unfavorable conditions. Moreover, along with other second messengers (such as ROS, calcium, nitric oxide, cyclic nucleotides, etc.), GSH also acts as a cellular signal involved in stress signal pathways in plants, directly or along with the glutaredoxin and thioredoxin systems. While associated biochemical activities and roles in cellular stress response have been widely presented, the relationship between phytohormones and GSH has received comparatively less attention. This review, after presenting glutathione as part of plants’ feedback to main abiotic stress factors, focuses on the interaction between GSH and phytohormones, and their roles in the modulation of the acclimatation and tolerance to abiotic stress in crops plants.